1987
DOI: 10.1063/1.98745
|View full text |Cite
|
Sign up to set email alerts
|

Deep level transient spectroscopy studies of epitaxial silicon layers on silicon-on-insulator substrates formed by oxygen implantation

Abstract: Deep level transient spectroscopy was applied to study silicon epitaxial layers of varying thickness grown on silicon-on-insulator substrates formed by oxygen implantation. For 3-μm-thick layers no traps were detected. For 1.0-, 2.0-, and 2.5-μm-thick layers electron traps were found with levels 0.34, 0.32, and 0.37 eV below the conduction-band edge, and corresponding capture cross sections of ∼2.0×10−7, 6.0×10−18, and 5.0×10−7 cm2. These levels were found to be uniformly distributed across the wafer. It was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Considering the aforementioned results on SIMOX SOI layers wherein the deep levels are completely annealed out when the annealing temperature is higher than 1250ЊC, [5][6][7] the observations in this work are rather contradictory. However, it should be noted that there are big differences in the sample structure and thermal cycles involved after oxygen implantation when compared to the previous works.…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…Considering the aforementioned results on SIMOX SOI layers wherein the deep levels are completely annealed out when the annealing temperature is higher than 1250ЊC, [5][6][7] the observations in this work are rather contradictory. However, it should be noted that there are big differences in the sample structure and thermal cycles involved after oxygen implantation when compared to the previous works.…”
Section: Resultsmentioning
confidence: 62%
“…The high-temperature annealing behaviors of deep levels in the SIMOX SOI layer have been studied in previous research. [5][6][7][8][9] At annealing temperatures higher than 1300ЊC, it has been reported that the physical defects, which could be associated with deep levels in the SOI layer, completely disappeared. However, most research investigated deep levels in thick (>0.4 m) epitaxially grown SIMOX SOI layers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Low-energy oxygen ions (¾0.1-20 keV) also are employed in SIMS to determine the depth distribution of impurities in semiconductors. The formation of a stoichiometric surface oxide layer may cause the redistribution of the impurity species being profiled, and hence degrade the depth resolution.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 It is, however, well known that the use of ion implantation in the formation of SIMOX SOI creates damage in the Si lattice, which is stable even after annealing. 3,4 Low-energy oxygen ions (¾0.1-20 keV) also are employed in SIMS to determine the depth distribution of impurities in semiconductors. The formation of a stoichiometric surface oxide layer may cause the redistribution of the impurity species being profiled, and hence degrade the depth resolution.…”
Section: Introductionmentioning
confidence: 99%